Microenvironment-derived factors driving metastatic plasticity in melanoma - Isabella S. Kim (Nature Portfolio, 2017)
Phenotype switching is a form of plasticity that allows melanoma cancer cells that leave the primary tumour to invade secondary sites, to switch from an invasive to a proliferative state. Here the authors identify EDN3, and its synthetic enzyme ECE2, as a regulator of melanoma plasticity in the microenvironment.